A Rare and Emerging Entity: Sinonasal IgG4–related Sclerosing Disease. Issue 3 (September 2015) - Song, Brian H.; Baiyee, Daniel; Liang, Jonathan
Background: Immunoglobulin G4 (IgG4) related sclerosing disease (rSD) is a new disease entity, first described in 2001, that involves autoimmune pancreatitis. Considered a systemic disease with lesions described in multiple organ systems, IgG4-rSD that affects the sinonasal region is rare. Our goal was to highlight the sinonasal presentation of this unique disease and to review previously reported adult cases from 2003 to 2014. Methods: Case report (a 72-year-old man who presented with left exophthalmos, periorbital pain, and epiphora) and review of the literature. Results: Radiographic workup with computed tomography and magnetic resonance imaging demonstrated a left sinonasal mass that involved the left maxillary and ethmoid sinuses, with surrounding bony destruction and orbital invasion. Nasal endoscopy demonstrated a fibrous lesion emanating in the middle meatus, with surrounding mucosal inflammation. The patient underwent an endoscopic biopsy, medial maxillectomy, and ethmoidectomy with tumor debulking. Pathology demonstrated inflamed respiratory mucosa with dense lymphoplasmacytic infiltrate and fibrosis; flow cytometry demonstrated no malignant cell populations; immunophenotyping demonstrated multiple foci of IgG4 cells. Plasma IgG4 was elevated in the setting of normal total IgG. The patient was treated with postoperative systemic and topical corticosteroids. Surveillance imaging studies and nasal endoscopy demonstrated disease resolution without recurrence. Conclusions: Sinonasal IgG4-rSD is a rare disease that can present with bony and soft-tissue invasion. This was an exceptional case, with osseous involvement and orbital invasion. Immunohistologic workup is essential for diagnosis. It is important to differentiate this disease from sinonasal tumors. Treatment includes corticosteroids and surgical debulking. Sinonasal IgG4-rSD represents an emerging disease that may present challenges for future rhinologists.